2017
DOI: 10.1039/c7nr03172f
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted peptide assisted one-pot synthesis of gold nanoparticles for plectin-1 targeted gemcitabine delivery in pancreatic cancer

Abstract: An astute modification of the plectin-1-targeting peptide KTLLPTP by introducing a C-terminal cysteine preceded by a tyrosine residue imparted a reducing property to the peptide. This novel property is then exploited to fabricate gold nanoparticles (GNP) via an in situ reduction of gold (III) chloride in a one-pot, green synthesis. The modified peptide KTLLPTPYC also acts as a template to generate highly monodispersed, spherical GNPs with a narrow size distribution and improved stability. Plectin-1 is known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 60 publications
(66 reference statements)
0
40
0
Order By: Relevance
“…These AuNPs were further functionalised with the chemotherapeutic drug gemcitabine (Gem), which adsorbs to the AuNP core through hydrophobic interactions, as well as forming a reversible Au-N bond. 97 These AuNPs show higher cytotoxicity towards PDAC cell lines than Gem alone and display excellent selectivity for PDAC cells over healthy tissue in mouse models. 97 This use of the YC dipeptide to simultaneously nucleate and cap AuNPs has also been used to form AuNPs for use as radiosensitisers.…”
Section: Peptide Directed Gold Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…These AuNPs were further functionalised with the chemotherapeutic drug gemcitabine (Gem), which adsorbs to the AuNP core through hydrophobic interactions, as well as forming a reversible Au-N bond. 97 These AuNPs show higher cytotoxicity towards PDAC cell lines than Gem alone and display excellent selectivity for PDAC cells over healthy tissue in mouse models. 97 This use of the YC dipeptide to simultaneously nucleate and cap AuNPs has also been used to form AuNPs for use as radiosensitisers.…”
Section: Peptide Directed Gold Nanoparticlesmentioning
confidence: 99%
“…97 These AuNPs show higher cytotoxicity towards PDAC cell lines than Gem alone and display excellent selectivity for PDAC cells over healthy tissue in mouse models. 97 This use of the YC dipeptide to simultaneously nucleate and cap AuNPs has also been used to form AuNPs for use as radiosensitisers. These AuNPs are targeted towards a v b 3 integrin expressing cells through the cyclic peptide c(RGD) (Fig.…”
Section: Peptide Directed Gold Nanoparticlesmentioning
confidence: 99%
“…This is explained by showing that GNPs inhibited epithelial to mesenchymal transition and reduced cancer cell stemness-possible causes of anticancer drug resistance [168]. Furthermore, Pal et al showed in Figure 9 that gemcitabine-conjugated GNPs that specifically target pancreatic cancer cells with a plectin-1 peptide have improved efficacy in situ compared to the free drug alone [169]. The use of gemcitabine with radiotherapy has also been shown to be more effective than the drug alone through clinical trials [170].…”
Section: Rationale For Gold Nanoparticles In Chemoradiotherapymentioning
confidence: 99%
“…(B) KI67, a marker for proliferation, also showed reduced proliferative cells when treated with the GNP complex compared to the free drug alone, signifying improved efficacy. Reproduced with permission from[169]. Copyright 2017 Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…PANC1 (item number CRL-1469 and batch number 62278038; ATCC) was cultured following a standard method, as described previously (36). Briefly, PANC1 was grown in DMEM supplemented with 10% FBS and 1% penicillin--streptomycin.…”
Section: Cell Culturementioning
confidence: 99%